SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN DALAM PERJANJIAN KREDIT - Asuan, Asuan (Faculty of Law, University of Palembang, 2021)
Power of Attorney Charging Mortgage Rights (SKMHT) the provision of credit / credit agreement (principal agreement) in a written agreement and the debtor with the creditor's approval, which guarantees the form of land rights and power of attorney to impose Mortgage Rights (SKMHT) and Deed of Granting Mortgage Rights (APHT) ). The power of attorney is special and authentic which must be made before a Notary or PPAT based on the provisions in Article 15 paragraph (1) of Law Number 4 of 1996 concerning Mortgage Rights. Barriers to the issuance of Power of Attorney to impose Mortgage Rights (SKMHT) and Deed of Granting Mortgage Rights (APHT) are very expensive / high costs and the land of the SKMHT object is not yet a land title certificate / has not been registered at the National Land Agency office.